French 2010–2011 measles outbreak in adults: report from a Parisian teaching hospital. (30th October 2013) - Caseris, M.; Houhou, N.; Longuet, P.; Rioux, C.; Lepeule, R.; Choquet, C.; Yazdanpanah, Y.; Yeni, P.; Joly, V.; Kaiser, L.
Abstract We reviewed 80 adult cases of measles seen in a Parisian hospital during the French 2010–2011 outbreak. Fifty per cent had at least one complication: pneumonia and hepatitis were the most frequent. Forty per cent of hospitalized cases did not have any complications, suggesting clinically poor tolerance of measles in adults. The outcome was always favourable. Subjects were younger, were more often French nationals and had a higher socio‐economic status than the overall population. This report suggests that immunity resulting from natural disease in patients from an area where the disease is endemic is protective in the long term.